Increasing Public Knowledge About Hypertension as an Effort to Prevent Hypertension Complications (Stroke) - Angriawan; Wati, Indah; Zuidah; Karokaro, Tati Murni; Simarmata, Juni Mariati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Hypertension is a health disorder that causes an increase in blood pressure. Hypertension can cause serious complications in the form of stroke. These significant complications can be life threatening and even death. Stroke is a global health problem with more than 15 million people annually experiencing this condition worldwide. This study was conducted on 30 individuals who visited the Pagar Jati Community Health Center, using the accidental sampling method, to explore the contribution of community participation in increasing awareness about hypertension and promoting preventive behavior. Through outreach activities and public campaigns, community participation has succeeded in increasing understanding of the importance of regular health check-ups by checking blood pressure and consuming foods with balanced nutrition, including low salt, thereby preventing hypertension. Evaluating the effectiveness of the community service program using a questionnaire showed an increase from 70% at the pretest stage to 93% at the posttest stage. This reflects a significant increase in awareness, knowledge and preventive measures against complications of hypertension, such as stroke, in the community areas served by health community center (Puskesmas) Pagar Jati. Collaboration between health workers, local government, educational institutions and the community is the key to the success of this program. Although challenges remain such as limited access and inequality of information, community service has proven to be an effective tool in strengthening the community response to hypertension and advancing overall community health.